Insect‐induced tree mortality of boreal forests in eastern Canada under a changing climate - Zhang, Xiongqing; Lei, Yuancai; Ma, Zhihai; Kneeshaw, Dan; Peng, Changhui (Ecology and Evolution, 2014)
Abstract Forest insects are major disturbances that induce tree mortality in eastern coniferous (or fir‐spruce) forests in eastern North America. The spruce budworm ( SBW ) ( Choristoneura fumiferana [Clemens]) is the most devastating insect causing tree mortality. However, the relative importance of insect‐caused mortality versus tree mortality caused by other agents and how this relationship will change with climate change is not known. Based on permanent sample plots across eastern Canada, we combined a logistic model with a negative model to estimate tree mortality. The results showed that tree mortality increased mainly due to forest insects. The mean difference in annual tree mortality between plots disturbed by insects and those without insect disturbance was 0.0680 per year ( P < 0.0001, T ‐test), and the carbon sink loss was about 2.87t C ha −1 year −1 larger than in natural forests. We also found that annual tree mortality increased significantly with the annual climate moisture index ( CMI ) and decreased significantly with annual minimum temperature ( T min ), annual mean temperature ( T mean ) and the number of degree days below 0°C ( DD 0), which was inconsistent with previous studies (Adams et al. ; van Mantgem et al. ; Allen et al. ). Furthermore, the results for the trends in the magnitude of forest insect outbreaks were consistent with those of climate factors for annual tree mortality. Our results demonstrate that forest insects are the dominant cause of the tree mortality in eastern Canada but that tree mortality induced by insect outbreaks will decrease in eastern Canada under warming climate.